IMPLEMENTASI PRINSIP PERADILAN CEPAT, SEDERHANA DAN BIAYA RINGAN DALAM PERKARA PERDATA DI PENGADILAN NEGERI SAMARINDA - Marudut Hasiholan Pasaribu (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTDistrict Court in carrying out its duties to enforcing the law and justice must meet the expectations of the seekers of Justice always requires the judiciary are simple, quick and light costs. Article 2 paragraph (4) Act No. 48 of the year 2009 about the fine points of power of Justice formulates that the judiciary is done with a simple, fast and light costs. The writing is aimed at knowing the District Court Samarinda are already running in accordance with the principle of Justice is fast, simple and light-weight and cost to find out what the constraints faced by the District Court of Samarinda in the exercise of civil litigation matters in accordance with the principle of Justice is fast, simple and light costs. Research results are obtained, the implementation of the principle of Justiceis fast, simple and light costs in civil litigation in the courts of the country already well done Samarinda, based on the results of the research the author of finalization of the average lawsuit civil litigation in the District Court of Samarinda does not exceed the time limit set by the SEMA number 2 Year 2014. Constraints are faced with State Court judicial principles to realize Samarinda fast, simple and light is the factor of absence of the parties on the day of the trial, witness the large number of factors that must be presented by the parties and the presence of a witness or of proof that is often delayed.Keywords: Implementation of the principle of Perdilan is fast, simple and Light Costs